Measuring Populist Communication Discourse of the 2024 Indonesian Presidential Candidates’ Campaigns on Social Media - Nicolas Kriswinara Astanujati (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2026)
In the recent Indonesian presidential election, social media became a battleground for political campaigns, and candidates were often labelled as populists. This article challenges those claims by examining discursive patterns in the social media content of the 2024 presidential candidates on X (formerly Twitter ). The study investigates three candidates: Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo through a dataset of posts (N = 792). Using quantitative content analysis based on Cassell’s (2020a) discursive framework, the study categorises content into four master frames: populism, pluralism, technocracy, and neutrality, along with 13 related rhetorical elements. This approach allows for mapping of both populist and non-populist communication discourses, addressing the limitations of qualitative methods alone. The findings differ from the expected populist narrative. While each candidate possesses a unique frame of discourse, neutral element patterns emerged as the most frequently employed among all candidates. They turned formal political discourse into “everyday politics” by drawing on daily activities and positive emotions in their X content. This strategy reflects two sides of a coin. On the one hand, it allows candidates to build an approachable and relatable persona, while on the other, it reduces constructive and critical debate on policy and politics. This study argues that the rise of the “everyday politician” signals a transformation in Indonesian campaign strategies, one that actively depoliticises campaign discourse and poses a direct challenge to how populism is defined and measured within the evolving landscape of the digital public sphere.